The Role of the Tulang Bawang Police Drug Investigation Unit in Implementing the Rehabilitation Program for Drug Abuse Based on Article 127 of Law Number 35 Year 2009 on Narcotics - Jainah, Zainab Ompu; Hakim, Lukmanul; Suryana, Agus; Anjaya, Reja; Bisri, Mirza (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
The role of the Tulang Bawang Police Narcotics Investigation Unit (Sat Res Narkoba) is very strategic in handling narcotics problems in its jurisdiction. Not only enforcing the law against perpetrators, Sat Res Narkoba also plays an important role in implementing rehabilitation programs for drug abusers. The formulation of the problem in this study is how is the role of Sat Res Narkoba Polres Tulang Bawang in implementing rehabilitation programs based on Article 127 of Law Number 35 of 2009 concerning Narcotics, and what are the inhibiting factors. This study uses a normative and empirical legal approach, with primary and secondary data obtained through literature studies and field research, and analyzed qualitatively. The results of the study indicate that the role of Sat Res Narkoba is very important in implementing rehabilitation, but its success requires cross-sector synergy, including rehabilitation institutions, families, and communities. Inhibiting factors include unclear regulations, limited budget and facilities, and low understanding of the law and negative stigma against drug abusers. It is recommended that the Narcotics Research Unit take strategic steps in implementing rehabilitation programs, and that local governments together with related agencies strengthen synergy through communication forums, counseling, and family empowerment.